High-temperature oxidation behavior of carbon doped CoCrNi medium entropy alloy fabricated by laser powder bed fusion - Soobin Kim; So-Yeon Park; Kee-Ahn Lee (Journal of Materials Research and Technology)
The oxidation behaviour of two CoCrNi medium entropy alloys with carbon contents of 0.25 at% and 0.75 at% (0.25C MEA and 0.75C MEA) was investigated. These alloys were designed via laser powder bed fusion (L-PBF) to enhance mechanical properties by controlling in-situ nano precipitates. High-temperature oxidation tests were conducted at 900, 1000, and 1100 °C for 24 h in an air-like atmosphere. The 0.25C MEA exhibited weight changes of 0.052–0.852 mg/cm2, while the 0.75C MEA showed higher changes of 0.256–1.148 mg/cm2, highlighting the significant impact of carbon on oxidation resistance. Carbide formation was suggested to play an important role in determining internal oxidation behaviour.